Prognostic relevance of prospero homeobox 1 and metastasis tumor antigen 1 in patients with malignant salivary gland tumors: a clinicopathological study - Samar Soliman; Doaa Abdallah Farag; Heba Ahmed Elhendawy (European Journal of Medical Research)
Abstract Objective The current study aimed to investigate the prognostic relevance of PROX1, and MTA1 in salivary gland carcinomas. Methods In a retrospective study on 45 cases diagnosed with salivary gland carcinoma, PROX1 and MTA1 immunoexpressions were assessed concerning the different clinicopathologic parameters, disease-free (DFS), and overall survivals (OS). Pearson’s Chi-square test, One-way ANOVA, and Post Hoc tests were used to estimate the difference between groups. The Kaplan–Meier method was used to record DFS and OS, and the log-rank test was used to analyze the data. With Cox regression, univariate and multivariate survival analyses were run. A P-value of 0.05 or less was regarded as statistically significant. Results Positive PROX1 and high MTA1 expressions were significantly associated with large tumor sizes (T3 & T4), presence of nodal and distant metastasis, advanced TNM clinical stage (III + IV), and presence of tumor recurrence (P values were ≤ 0.05). Moreover, positive PROX1, and high MTA1 expressions were significantly associated with poor DFS and OS in the univariate models. Additionally, DFS and OS were significantly reduced in relation to large sized tumors (T3 + T4), positive nodal involvement, positive distant metastasis, advanced TNM clinical stage (III + IV), high-grade carcinomas, presence of LV invasion, and old ages (P values were ≤ 0.05). The multivariate analysis with Cox regression found that distant metastasis was the independent predictor for DFS, but not for OS in SGC patients. Conclusions PROX1 and MTA1 immunoexpression could be used as predictors of progression and recurrence in SGC patients. PROX1 and MTA1 are potentially prognostic, predictive biomarkers, and promising molecular therapeutic targets in SGC patients. Trial registration Retrospectively registered.